Socio-economic impact of soil water conservation measures at Thatipura panchayat of Chambal region - KUSHWAHA, T. S.; SINGH, Y. P.; SINGH, SUDHIR; SINGH, A. K. (Journal of Soil and Water Conservation, 2020)
A comprehensive study was carried out after two years of watershed works to assess of developmental activities in ravine affected area of Chambal region of Madhya Pradesh. Study revealed that the drastic change was noted in cropping intensity, agricultural production, annual income and employment. The rainwater conservation in check dams, tanks, gully plugs and khet talab had a great impact on the changes in area of irrigation with stored water and recharges of ground water. The water table increased by 6.1 feet as compared with before rain water conservation activities. After rainwater management practices the irrigated area was 169 ha, whereas 35 ha before the project. Resulting increased in cropping intensity from 159 to 195%. Study revealed that maximum area of pearl millet increased followed by short duration pigeon pea in rainy season crops. As regards in winter season crops acreages was increased considerably in case of wheat (144%) followed by mustard (118%). The increase in yield was 21 to 59% of rainy season crops, like wise 12 to 60% of winter season crops. Farmers started raising more remunerative crops as well as vegetable crops, fodder for milch animals and consequently their annual income increased by 156%. Also, there was a significantly higher employment generation, check the migration and overall prosperity. Intangible benefits recharging of ground water had decreased salinity/alkalinity of ground water as well as also checks the formation of ravine land through control of soil erosion, which is serious problem of Chambal division of Madhya Pradesh.